Biocompatibility and biodegradation of polyester and polyfumarate based-scaffolds for bone tissue engineering - Cortizo, María Susana (2008)
Biodegradable and biocompatible polymeric scaffolds have been recently introduced for tissue regeneration purpose. In the present study we aimed to develop polymeric-based scaffolds for bone regeneration. Two polyesters, poly-β-propiolactone (PBPL), poly-ε-caprolactone (PCPL) and two polyfumarates, polydiisopropyl fumarate (PDIPF), polydicyclohexyl fumarate (PDCF) were chosen to prepare films which can support osteoblastic growth. Scanning electron microscopy and water contact angle were used to characterize the matrices. Biodegradation studies were performed both in PBS buffer and using an in vitro macrophage degradation assay. Mouse calvaria-derived MC3T3E1 cells and UMR106 rat osteosarcoma cell lines were used to perform biocompatibility and cytotoxicity studies. The polyesters, the most hydrophilic polymers studied, showed a rougher and more porous surfaces than the polyfumarates. Under acellular conditions, only PBPL was degraded by hydrolytic mechanisms. However, macrophages performed an active degradation of all polymeric films. Osteoblasts developed well-defined actin fibres without evidence of cytotoxicity when growing on the films. The number of UMR106 osteoblasts that adhered to the PBPL-based film was higher than that of the cells attached to the PECL and polyfumarates (PDIPF and PDCF) matrices. Both UMR106 and MC3T3E1 osteoblastic lines showed protein levels comparable to control conditions, demonstrating that they grew well on all surfaces. However, UMR106 cells showed a significant increase in proliferation on polyester-derived scaffolds (PBPL and PECL). The alkaline phosphatase activity of UMR106, an osteoblastic marker, was significantly higher than that of control plastic dishes. MC3T3E1 cells expressed similar levels of this differentiation marker in all polymeric matrices. We found similar collagen protein content after 48 h culture of UMR106 cells on all surfaces. However, important differences were evident in the MC3T3E1 line. In conclusion, the synthetic polymeric-based scaffold we have developed and studied supports adhesion, growth and differentiation of two osteoblastic cell lines, suggesting that they could be useful in bone tissue regeneration.